The Effect Of Education Using Workbook On Self-Efficacy Of The Coronary Heart Disease Management In Acute Phase And Two Weeks Post Heart Attack - Adinda Utami; Aan Nur’aeni; Imas Rafiyah (Journal of Nursing Care, 2020)
Background. Self-efficacy needed by Coronary Heart Disease (CHD) patients as a first step in managing the disease. Education is given as an effort to increase patients’ self-efficacy, but the media for education is limited. The workbook is an educational media that would encourage patients’ roles, overcome obstacles and increase the self-efficacy of CHD patients. Purpose. This study aimed to determine the differences in self-efficacy of CHD patients before and after the health education using a workbook. Method. This study was a quasi-experimental study with a pre-test post-test control group design. The samples were 19 patients in the CICU room at a hospital in the city of Bandung that chosen using a purposive sampling technique. The intervention group received health education using media workbooks (n=9) and then another group was the control group (n=10). Self-efficacy was measured using a questionnaire Self-efficacy CHD Management. Data were analyzed using frequency distribution and bivariate using Wilcoxon and Mann Whitney tests. Results. The study found p-value from the Wilcoxon test in the intervention group was 0.008 (p <0.05) while the control group was 0.102 (p> 0.05). The results of the Mann Whitney test showed that before the intervention, the p-value between the intervention group and the control group was 1,000 (p> 0.05), whereas after the intervention the p-value between the two groups was 0.040 (p <0.05). Conclusion. Based on the results of the study, there are significant differences in self-efficacy between the two groups. The health education method using a workbook can be used to improve the self-efficacy of CHD patients.